Trisomy 5p with bilateral congenital diaphragmatic hernia: a case report - Noriyuki Nakamura; Takafumi Ushida; Yoshinori Moriyama; Kenji Imai; Tomoko Nakano-Kobayashi; Satoko Osuka; Maki Goto; Hiroaki Kajiyama; Hideyuki Asada; Masahiro Hayakawa; Tomomi Kotani (Journal of Medical Case Reports, 2021)
Abstract Background Bilateral congenital diaphragmatic hernia (CDH) is very rare. A few studies have reported the pathogenic role of 5p in CDH. Case presentation A 23-year-old primigravida Japanese woman was referred for the following abnormal findings at 33 weeks of gestation: polyhydramnios, macroglossia, talipes equinovarus, and levocardia. A marker chromosome was detected by amniocentesis. Fluorescence in situ hybridization with whole chromosome paint 5 and nucleolus organizer region probes confirmed its origin from chromosome 5 and an acrocentric chromosome. The karyotype of the fetus was diagnosed as 47, XY, +mar. ish +mar(WCP5+). At 39 + 5 weeks, a 2462 g male infant was delivered, with a specific facial configuration. Bilateral CDH, hypoplasia of the corpus callosum, atrial septal defect, and hypothyroidism were also detected in the baby. The karyotype of the peripheral blood was consistent with that of the amniocentesis. Conclusion Genes coded on 5p might be associated with the pathogenesis of CDH; however, further investigation is required.